Web-Based Information System of BPJS Patient Referral Letter in UPT Puskesmas Gumuruh - Shabita Safhira; Wilda Indriyani; Dina Sonia (STAI Miftahul Ula Nganjuk, 2022)
In fact there are still some of factors that for the referral late, as the occurence of, obstructed labor the difficulty of the decision-making process related to the economic aspect and transportation costs, and the aspect of geographic and availability of infrastructure hospital. This study attempts to analyze the supporters and the barrier covering input and process in the referral system patients BPJS at UPT Puskesmas Gumuruh. A method of made in this study is the method field, a method of literature and method of development systems which is waterfall. The result showed that the lack of facilities and services at UPT Puskesmas Gumuruh still experienced limited supplies and unsatisfactory.The referral online at health facilities first degree is expected to ease patients to obtain, referral letter there is one problem in registration and making. Therefore, the authors designed a web-based BPJS patient referral letter information system to make it easier for patients to obtain hospital services tailored to competence, distance, and capacity according to patient needs. The puskesmas, health offices and BPJS Health need to work together to disseminate information regarding the referral system and pay attention to the provision of drugs and health facilities to maximize the implementation of the referral system.